Constraints and Suggestions for Effective Implementation of Farm Women Development Programmes - K. Atchuta Raju; G. Sowjanya Roy; T. Sarah Kamala; M. Sudha Rani (Journal of Agricultural Extension Management, 2025)
Women’s contribution to national development is crucial. The process of development would be incomplete and lopsided, unless women are fully involved in it. Emancipation of women is an essential pre-requisite for economic development and social progress of the nation. If any programme has to be implemented successfully, so that certain modifications if any needed for the improvement of the programme can be taken into consideration. Women development programmes are facing problems of traditional and cultural norms, lack of marketing and storage facility, finance, inadequate supply of inputs, lack of viable schemes, and less importance to agricultural programmes. The success or failure of any programme can be shown by assessing the reactions of the people involved in that programme. The effectiveness of different development programmes depends on the women only, how vocal are they, how effective are they in taking decisions to their favours in male dominated panchayats so that there is some reduction in the arduous task faced by poor women. This study was designed with the objective to analyse the constraints